Rehabilitasi Kasus Kelas I Kennedy Rahang Atas dengan Gigi Tiruan Kaitan Presisi (Precision Attachment) - Ruby Karyadi; Laura Susanti Himawan (Faculty of Dentistry, Universitas Indonesia, 2015)
The most important reason for employing an extracoronal precision attachment in bilateral free end saddle denture is to fulfill the esthetic demands of the patient and the dentist. In this case, splinted crowns were fabricated for the remaining teeth (13, 12, 11 and 21, 22, 23) after tooth 13 had been endodontically treated. An extracoronal retainer (ceka anker) was placed for tooth 13 and 23. Patient, male, aged 60, was very pleased with his new upper denture.